2021
DOI: 10.1002/ldr.4066
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage and organic nutrients management improve soil properties, productivity, and economics of a maize‐vegetable pea system in the Eastern Himalayas

Abstract: Soil quality restoration and sustainable crop production in the rainfed ecosystem of the Indian Himalayas can be achieved through effective conservation tillage and organic management. Hence, a six-year (2013 to 2019) study was conducted to quantify the effect of tillage and organic nutrient management on soil properties, productivity, and profitability of the maize-vegetable pea (Pisum sativum) system.Three tillage practices [conventional (CT), reduced (RT), and no-till (NT)] and four organic nutrients manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…Higher crop productivity under no-till system over conventional tillage across different ecologies has been reported by many researchers (Yadav et al 2020, Singh et al 2021b). Similar higher system productivity under maize-pea system was reported by Singh et al (2021a). Kumar et al (2019b) also reported that rice-green gram system enhanced the system profitability and production efficiency by 126% and 307%, respectively than rice fallow.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Higher crop productivity under no-till system over conventional tillage across different ecologies has been reported by many researchers (Yadav et al 2020, Singh et al 2021b). Similar higher system productivity under maize-pea system was reported by Singh et al (2021a). Kumar et al (2019b) also reported that rice-green gram system enhanced the system profitability and production efficiency by 126% and 307%, respectively than rice fallow.…”
Section: Resultssupporting
confidence: 75%
“…While under rice-fallow where proper tillage is adopted breaks soil aggregates and subsequently exposes the stored carbon in macro and micro aggregates to a microorganism for further decomposition and mineralization processes resulting in low soil organic carbon (Yadav et al 2019). Hence, the no-till practices favoured the accumulation of SOC which may enhance the nutrients accumulation and mobilization (Singh et al 2021a). The accumulation of higher SOC under this experiment was due to more root biomass inclusion through garden pea in rice-based system.…”
Section: Ricementioning
confidence: 76%
“…Agricultural management strategies those are sustainable from an ecological perspective are essential to the continued provision of ecosystem services ( 4 , 40 ). The designing of a food and nutrient-efficient cropping system to sustain the livelihood of farmers will achieve little toward SDGs-3 (good health and wellbeing) and-12 (zero hunger; responsible consumption and production).…”
Section: Discussionmentioning
confidence: 99%
“…Mamadou et al (2015) and Abdourhamane Touré et al (2019) attribute this phenomenon to soil leaching induced by erosive hazards (water and wind) that can increase soils vulnerability by removing the finest and most fertile soil particles including nutrients. Improving the organic matter content of degraded land requires the implementation of biological techniques including mulching or the use of organic manure (Liu et al, 2014; Singh et al, 2021). In the case of particle size distribution, a significant impact on the texture of developed soils was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the Sahel, soils organic matter depletion is mainly attributed to high mineralization linked to pedoclimatic factors (Pallo et al, 2009). Mamadou et al (2015) and Abdour- mulching or the use of organic manure (Liu et al, 2014;Singh et al, 2021). In the case of particle size distribution, a significant impact on the texture of developed soils was observed.…”
Section: Impacts Of Erosion Control Measures On the Physicochemical P...mentioning
confidence: 99%